DIPLOMASI PERDAGANGAN PALA MALUKU UTARA KE BELANDA PADA TAHUN 2015-2020 - Dhanis Wirasati Dewi Handayani; Christy Damayanti; Untari Narulita Madyar Dewi (UIN ALAUDDIN MAKASSAR, 2022)
The main supplier of Nutmeg imported by the Netherlands is the North Maluku region. However, in the period of 2016, the demnad for Nutmeg exports experienced a drastic decline due to regulations set by the European Union. This regulations is related to food safety and hygiene as stipulated by the RASFF (Rapid Alert System Food and Feed) which is a system owned by the European Union was noted that Indonesia recived several warnings regarding the Nutmeg comodity exported to the Netherlands that contained alflatoxin too much, which caused the export of Nutmeg from North Maluku to decline. The problem formulation of this research is how the trade diplmacy of North Maluku Nutmeg to Netherlands in 2015-2020. Thus research use the analysis of diplomacy theory with a focus on the concept of trade diplomacy and international trade theory. From this research, it can be conclude that the indonesian state must attach a health certificate from food supervisory agency stating that the exported from North Maluku Nutmeg comodity meets the maximum standard of aflatoxins.